Protective effects of tumor necrosis factor α antibody and ulinastatin on liver ischemic reperfusion in rats - Yang, Yan-Ling (World J Gastroenterol, 2004)
AIM: To study the protective effects of tumor necrosis factor α (TNF α ) antibody and ulinastatin on liver ischemic reperfusion in rats. METHODS: One hundred and twenty male SD rats were randomly divided into four groups: Normal control group, ischemic group, TNFα antibody group and TNFα antibody + ulinastatin group. The animals were killed at 0, 3, 6, 9, 12 h after ischemia for 60 min and followed by reperfusion. Serum alanine aminotransferase (ALT), malondialdehyde (MDA) and liver histopathology were observed. RESULTS: After ischemic reperfusion, the serum ALT and MDA were remarkably increased, and the hepatic congestion was obvious. Treatment of TNFα antibody and ulinastatin could significantly decrease serum ALT and MDA levels, and relieve hepatic congestion. CONCLUSION: Ulinastatin and TNFα antibody can suppress the inflammatory reaction induced by hepatic ischemic reperfusion, and have protective effects on rat hepatic ischemic reperfusion injury.